The performance environment of the England youth soccer teams - Pain, M. A.; Harwood, C. (Journal of Sports Sciences, 2007)
In the present study, we examined the performance environment of the England youth soccer teams. Using a semi-structured protocol with a prospective sample, national coaches (n = 6), sport scientists (n = 3), and players (n = 4) were interviewed directly following international tournaments about the factors that positively and negatively influenced performance. Qualitative content analysis revealed the following factors as major positive influences on performance: adhering to a consistent tournament strategy, player understanding, strong team cohesion, organized entertainment activities, detailed knowledge of opposition, an effective physical rest/recovery strategy, and previous tournament experience. Major factors perceived to have negatively influenced performance included: over-coaching, player boredom, player anxiety, physical superiority of the opposition, physical fatigue over the tournament, problems sleeping, and lack of information on the opposition. Eight overall dimensions emerged to describe the performance environment: planning and organization, physical environment, tactical factors, development and performance philosophy, psychological factors, physical factors, social factors, and coaching. The findings support recent work that suggests the performance environment is multifaceted, with performance being contingent upon a broad range of interacting factors that go beyond the traditional psychosocial and physical domains.